Overview on the Bacterial Iron-Riboflavin Metabolic Axis - Sepúlveda Cisternas, Ignacio; Salazar, Juan C.; García-Angulo, Víctor A. (Frontiers in Microbiology, 2018)
Redox reactions are ubiquitous in biological processes. Enzymes involved in redox metabolism often use cofactors in order to facilitate electron-transfer reactions. Common redox cofactors include micronutrients such as vitamins and metals. By far, while iron is the main metal cofactor, riboflavin is the most important organic cofactor. Notably, the metabolisms of iron and riboflavin seem to be intrinsically related across life kingdoms. In bacteria, iron availability influences expression of riboflavin biosynthetic genes. There is documented evidence for riboflavin involvement in surpassing iron-restrictive conditions in some species. This is probably achieved through increase in iron bioavailability by reduction of extracellular iron, improvement of iron uptake pathways and boosting hemolytic activity. In some cases, riboflavin may also work as replacement of iron as enzyme cofactor. In addition, riboflavin is involved in dissimilatory iron reduction during extracellular respiration by some species. The main direct metabolic relationships between riboflavin and iron in bacterial physiology are revised here.